2016
DOI: 10.3171/2016.1.spine151330
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation rates for symptomatic nonunions in posterior cervicothoracic fusions with and without bone morphogenetic protein in a cohort of 450 patients

Abstract: OBJECTIVE Fusions across the cervicothoracic junction have been challenging because of the large biomechanical forces exerted resulting in frequent reoperations for nonunions. The objective of this study was to investigate a retrospective cohort using chart review of posterior cervicothoracic spine fusions with and without bone morphogenetic protein (BMP) and to determine the reoperation rates for symptomatic nonunions in both groups. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…14,15,18,19,25 The majority of these studies report a higher radiographic fusion rate with BMP, but there may not be a substantial difference in clinically significant nonunion—defined as pseudarthrosis requiring revision—between these groups. 18,19,25 This question of clinical significance is important and is particularly relevant to the subject of BMP. The Yale Open Data Access (YODA) Project, for example, found that the use of BMP likely leads to an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,18,19,25 The majority of these studies report a higher radiographic fusion rate with BMP, but there may not be a substantial difference in clinically significant nonunion—defined as pseudarthrosis requiring revision—between these groups. 18,19,25 This question of clinical significance is important and is particularly relevant to the subject of BMP. The Yale Open Data Access (YODA) Project, for example, found that the use of BMP likely leads to an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, focusing on posterior BMP use at the cervicothoracic junction, found that the use of BMP did not result in a significantly different rate of symptomatic non-union requiring reoperation. 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] In clinical studies, the application of BMP demonstrated consistent osteoinduction which resulted in the "off-label" use of BMP in more than 85% of various spinal fusions. [11][12][13][14] Huang et al were able to show that recombinant human BMP (rhBMP)-2 created an increased inflammatory state in histological tissue sections and systemic blood samples of rats who had subcutaneously implanted BMP. [15] We postulate that these proinflammatory properties of BMP lead to increased healing rates by scarring and closure of the CSF fistula.…”
Section: Introductionmentioning
confidence: 99%
“…Reoperation rates for symptomatic nonunions (operative nonunions) is one way of combining the clinical and radiographic information. Several studies have shown measuring operative nonunion rates can be useful for comparing fusion techniques 33–36 …”
mentioning
confidence: 99%